Hysteroscopy and the risk of gas embolism: A review. Issue 1 (March 2020) - Ratner, Roni T; Tsaltas, Jim; Vollenhoven, Beverley
Hysteroscopy is one of the most frequent procedures that a gynecologist will perform over their career. It is also one of the safest procedures. Operative hysteroscopy has an increased risk profile due to the nature of the surgery. The following review will address the issue of gas embolism in hysteroscopy. This review will look at the evidence regarding the likely causation, rates, and potential methods of minimizing risk to patients as well as treatment options available should this complication arise.